2009
DOI: 10.1111/j.1464-410x.2009.08551.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences among patients undergoing perineal or retropubic radical prostatectomy in pain and perioperative variables: a prospective study

Abstract: level, Gleason score and clinical stage. Pain after RP was evaluated using numerical and oral scales, and by morphine intake delivered by a patient-controlled analgesia pump. Perioperative features assessed prospectively were operating time, intraoperative bleeding, time to diet, time to ambulation, hospital stay and complications. Immediate oncological results were assessed based on histopathological evaluation, e.g. Gleason score, tumour volume, prostate volume, surgical margins and final pathological stage.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
1
7
0
3
Order By: Relevance
“…In addition, all patients received gabapentin 600 mg pre‐operatively. Pain (VAS) scores in our control group (receiving the basic analgesic regimen with placebo‐TAP and placebo‐wound infiltration) were below 30 mm at all time points at rest, but 30–40 mm during mobilization in the first four post‐operative hours, which is comparable with findings from other studies of ORRP . It is well known that adequate assay sensitivity in acute pain trials may only be achieved when patients are experiencing at least ‘moderate pain’, which has been estimated to correspond to 30 mm on a VAS scale .…”
Section: Discussionsupporting
confidence: 84%
“…In addition, all patients received gabapentin 600 mg pre‐operatively. Pain (VAS) scores in our control group (receiving the basic analgesic regimen with placebo‐TAP and placebo‐wound infiltration) were below 30 mm at all time points at rest, but 30–40 mm during mobilization in the first four post‐operative hours, which is comparable with findings from other studies of ORRP . It is well known that adequate assay sensitivity in acute pain trials may only be achieved when patients are experiencing at least ‘moderate pain’, which has been estimated to correspond to 30 mm on a VAS scale .…”
Section: Discussionsupporting
confidence: 84%
“…Because of widespread use of PSA, predictability of rates of lymph node metastasis using various nomograms including Partin's, questionable necessity, and value of PLND in low-risk prostate cancer, lesser pain, and shorter hospital stay in RPP in comparison to RRP, RRP has rapidly dropped down the scale of desirability. [10,11] Thanks to comparable oncological, and functional outcomes between RPP, and RRP, minimally invasive, and cost-effective characteristics of RPP, as asserted in many current updated articles, RRP has been withdrawn from the therapeutic armamentorium of localized PCa. [12] In a review article, Coelho et al [13] analyzed the results of the studies related to retropubic, laparoscopic, and robot-assisted radical prostatectomies performed in high-volume centers where patients who didn't use daily urinary pads or employed only one urinary pad a day for the purpose of control of dryness during one-year follow-up period were considered to be continent, and authors reported continence rates for RRP, LRP, and RYRP, as 79, 84.8, and 92%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Schmeller and Paiva reported that no analgesics were needed starting from post-operative day 2. We believe that it does not lead to common pain issues experienced after a robotic prostatectomy (such as delays in return of the bowel movements) due to the small incision size, that the location of incision is not directly involved in mobilization, and the lack of abdominal gas insufflation (78,79).…”
Section: Post-operative Painmentioning
confidence: 99%